Epstein-Barr virus (EBV)-associated lymphoproliferative disease in the SCID mouse model: implications for the pathogenesis of EBV-positive lymphomas in man (The Rockefeller University Press, 1991)
When human peripheral blood lymphocytes (PBLs) from Epstein-Barr virus (EBV)-seropositive donors are injected intraperitoneally into SCID mice, EBV+ B cell tumors develop within weeks. A preliminary report (Mosier, D. E., R. J. Gulizia, S. M. Baird, D. D. Richman, D. B. Wilson, R. I. Fox, and T. J. Kipps, 1989. Blood. 74(Suppl. 1):52a) has suggested that such tumors resemble the EBV-positive malignancy, Burkitt's lymphoma. The present work shows that generally the human (hu) PBL-SCID tumors are distinct from Burkitt's lymphoma and instead resemble lymphoblastoid cell lines (LCLs) generated by EBV-infection of normal B cells in vitro in terms of: (a) their cell surface phenotype, with expression of B cell activation antigens and adhesion molecules, (b) normal karyotype, and (c) viral phenotype, with expression of all the transformation-associated EBV latent proteins and, in a minority of cells, productive cycle antigens. Indeed, in vitro-transformed LCLs also grow when inoculated into SCID mice, the frequency of tumor outgrowth correlating with the in vitro growth phenotype of the LCL which is itself determined by the identity of the transforming virus (i.e., type 1 or type 2 EBV). Histologically the PBL-derived hu-SCID tumors resemble the EBV+ large cell lymphomas that develop in immuno- suppressed patients and, like the human tumors, often present at multiple sites as individual monoclonal or oligoclonal foci. The remarkable efficiency of tumor development in the hu-SCID model suggests that lymphomagenesis involves direct outgrowth of EBV- transformed B cells without requirement for secondary genetic changes, and that selection on the basis of cell growth rate alone is sufficient to explain the monoclonal/oligoclonal nature of tumor foci. EBV+ large cell lymphoma of the immunosuppressed may arise in a similar way.